COVID-19 pandemic shifted epidemiology for cancer screening sites: breast, cervix, colon, and rectum - Ishkinin, Yevgeniy; Kaidarova, Dilyara; Nazarbek, Serzhan; Zhylkaidarova, Alma; Ossikbayeva, Saniya; Mussina, Kamilla; Omarbayeva, Nazgul (Frontiers in Oncology, 2025)
BackgroundThis study aimed to assess the epidemiological changes in breast, cervical, colon, and rectal cancers in Kazakhstan before and during COVID-19, including early-onset cancer (EOC) diagnosed between the ages of 20 and 49, using data from the oncological service of the Republic of Kazakhstan for the 2017–2022 period.MethodsThe cohort comprised patients aged 20 to 49 years (EOC) and 50 years and older [late-onset cancer (LOC)] from the total number of patients diagnosed each year during the study period of 2017 to 2022 for breast, cervical, colon, or rectal cancer. In order to indicate a difference in one-time intervals and characterize the global trend over the entire study period, annual percentage change (APC) and average APC (AAPC) were calculated, respectively.ResultsBreast cancer detection rates increased by 22.8% for EOC and 15.9% for LOC from 2017 to 2022, and AAPC increased by 4.3% for EOC and 3.6% for LOC. During the COVID-19 restriction period, breast cancer detection rates decreased by 6.1% for EOC and 15.6% for LOC. Cervical cancer detection rates increased by 2.3% for EOC and 7.5% for LOC from 2017 to 2022, and AAPC increased by 0.9% for EOC and 1.6% for LOC. During the COVID-19 restriction period, cervical cancer detection rates decreased by 11.3% for EOC and 3.1% for LOC. Colon cancer detection rates increased by 18.4% for EOC and 14.3% for LOC from 2017 to 2022, and AAPC increased by 3.7% for EOC and 2.9% for LOC. During the COVID-19 restriction period, colon cancer detection rates decreased by 14.4% for EOC and 5.8% for LOC. Rectal cancer detection rates increased by 13.6% for EOC and 19.2% for LOC from 2017 to 2022, and AAPC increased by 3.0% for EOC and by 3.9% for LOC. During the COVID-19 restriction period, rectal cancer detection rates increased by 18.6% for EOC and decreased by 12.0% for LOC.ConclusionThe epidemiological indicators of population cancer screening worsened during the COVID pandemic; the detection rate decreased by 6.1% for breast EOC and 11.3% for cervical EOC, while there was an increase by 38.0% in EOC for colon cancer in men and by 8.0% in EOC for rectal cancer in men and 31.1% in women.